Supporting time-critical clients in scalable pub-sub systems. (3rd January 2011) - Ray, Sibabrata; Linderman, Mark H.; Zhang, Danyang
In a publish-subscribe environment like the Air Force Joint Battlespace Infosphere (JBI), information/data has to be efficiently and reliably transmitted between servers and clients. However, due to various reasons such as unexpected network traffic, hardware/software failure, etc., the overlay network of the system may require reconfiguration, leading to intolerable service interruption of information flow to time-critical applications. This paper proposes theoretical methods for providing temporary respite to the time-critical clients while the backbone network is under repair.